Analisis Hukum Islam terhadap Faktor Putusnya Tali Perkawinan (Analysis of Islamic Law on Factor of Marriage Divorce) - Novitasari, Choirunnisa Nur; Latifiani, Dian; Arifin, Ridwan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Marriage is one of the legal events and regulated in a marriage law which is part of a civil law and regulates a man and woman with the intention of living together for a long time according to the legal regulations stipulated in the law. Most of the contents or regulations regarding social intercourse, husband and wife are regulated in religious norms, decency, or modesty, but disputes often occur in the household, resulting in a divorce or breakdown of marital ties, breaking marriage contract due to the wishes of husband or wife or both because disharmony originating from the failure to exercise the rights and obligations of a husband or wife as per the applicable marriage law. When a husband and wife decide on the desire to divorce, they must be prepared to face the court. Because the legal complaints process can only be taken in court, the possibility of the problem being faced by a husband and wife who are going to divorce is complicated and has difficulties when going through the divorce path, this factor can be caused because they are legally blind. divorce which is basically complicated, complicated to drain a lot of funds. In Islamic law itself. Everything that leads to damage to the household is something that is hated by God, such as divorce. Divorce is a lawful act but is very hated by God. Basically, all religious teachings do not allow divorce. So it is recommended for Muslims to be able to maintain integrity, harmony in the household, and be able to solve existing problems in a peaceful manner, so that there is no divorce. The factors that cause divorce are biological factors, psychological factors, moral factors, economic factors, sociological factors.